The Effect of Procedural Fairness in Compensation on Employee Performance, with Extrinsic Work Motivation as a Mediating Variable - Evi Arianti; Anita Maharani; Neneung Ratna Hayati (Journal of Economics and Business UBS, 2026)
Employee performance in public sector organizations, particularly within the Central Statistics Agency (Badan Pusat Statistik [BPS]), is critical to institutional effectiveness in providing accurate statistical data for national development planning. Although employee performance at BPS across West Sulawesi Province is generally satisfactory, variations in performance scores among work units indicate the need to examine organizational and psychological factors, particularly compensation procedural justice and extrinsic work motivation. This study examined the effect of compensation procedural justice on employee performance, with extrinsic work motivation as a mediating variable among BPS employees in the province. The research employed a quantitative survey approach, with data collected through questionnaires distributed to 147 BPS employees throughout the province. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine the hypothesized relationships, including direct and indirect effects. The findings revealed that compensation procedural justice had no significant direct effect on employee performance. However, it had a significant positive effect on extrinsic work motivation, which significantly influenced employee performance. Extrinsic work motivation fully mediated the relationship between compensation procedural justice and employee performance. These findings indicate that compensation procedural justice should be viewed not merely as an administrative mechanism but also as a motivational instrument. Fair compensation procedures improved employee performance when they enhanced employees’ extrinsic work motivation. Theoretically, this study contributed to a deeper understanding of Equity Theory and Self-Determination Theory within the public sector context. Practically, the findings provided evidence-based recommendations for BPS and other government institutions in designing compensation and reward systems that are procedurally fair and effective in strengthening employee motivation and performance.